O raciocínio prático em Aristóteles - D'oca, Fernando Rodrigues Montes (2010)
The objective of this work is to explain how practical reasoning takes place in Aristotle. This is a delicate and controversial issue of the Aristotelian practical philosophy, since he did not dedicate any moment of his work the Stagirite to closely analyze the practical reasoning. In his Nicomachean Ethics, Aristotle deals with deliberation, prudence, and practical syllogism, but we do not see him coordinate these themes as a concluded whole in a theory of the practical reasoning. This research aims to do so in order to precisely determine how the practical reasoning of a moral agent works, since its beginning, in the apprehension of a conception of the good, until its conclusion, in the imminence of an action. To do so this work undertakes an analysis of important conceptions about the theory of practical reasoning. Initially, two preliminary themes are dealt with: happiness and moral virtue, and right in sequence it goes deeper in the theme of practical reasoning analyzing the concepts of deliberate choice, of deliberation, and, most of all, of prudential reason, seeing that its operation covers a considerable part of the practical reasoning of the moral agent. But practical reasoning is not completely explained only by understanding such themes neither can it be limited to the operation of prudential reason. The theory of practical syllogism also appears as an important element in the explanation of how practical reasoning works. As a result of this, a large part of this research is dedicated to discussing the role of practical syllogism in the corpus aristotelicum, as well as to understanding the relationship it establishes with deliberation. Given its role and identified the kind of relationship it has with deliberation a complete map of practical reasoning is finally presented and the question about how practical reasoning in Aristotle works is then answered.